Forensic psychiatry evaluation in a U. S. immigration detention center in southwest Texas. (August 2019) - Ibrahim, Yasin; Singer, Elizabeth; Baronia, Regina; McMahon, Terry; Nelson, Jessica; Katz, Craig
Abstract: Immigration and asylum-seeking are issues that have recently. warranted increased attention and significance. In the aftermath of terrorist attacks, people are more wary of asylum seekers who are usually held in detention centers after fleeing persecution and not for criminal or immigration charges. Asylum seekers may raise suspicions due to inconsistent statements and can be held in detention for the duration of the process and/or denied asylum. Inconsistencies may be influenced by psychiatric symptoms, cognitive abilities, the type of past trauma experienced, the questioning style of the interviewer, and are usually unrelated to dishonesty or malingering making psychiatric consult important in many of these evaluations. Highlights: The assumption that inconsistency negates credibility is misguided. There are many factors, other than dishonesty, that can lead to inconsistencies. Calm demeanor of an asylum seeker does not negate history of torture or trauma. Cultural and educational background of asylum seekers can influence consistency. Consistency in core facts, not the peripheral ones, is relevant in decision-making.